ChemInform Abstract: Catalytic Selenium‐Promoted Intermolecular Friedel—Crafts Alkylation with Simple Alkenes. Issue 30 (July 2016) - Tang, E.; Zhao, Yinjiao; Li, Wen; Wang, Weilin; Zhang, Meng; Dai, Xin
Abstract: The title reaction uses TMSOTf as the catalyst and N‐phenylselenophthalimide as the selenium source to afford the selenenylated products in good yields with high regio‐ and diastereoselectivity.